The effect of the nitrogenous feeding form on some morphological and chemical characteristics and the productivity of maize planted in calcareous soil - مخيص شفيقة; عيسى كبيبو; نديم خليل; مازن أشرم (Latakia University Journal -Biological Sciences Series, 2022)
The research was carried out at the Dabba Research site of the Agricultural Scientific Research Center in Lattakia for the year 2020, to study the effect of three types of nitrogenous fertilizers (urea – ammonium sulfate – potassium nitrate) on some of the morphological and productive characteristics of the maize plant, variety Dina F1 planted in calcareous soil, in addition to the control treatment. Without adding nitrogen and at a rate of three replications for each treatment, the experiment was designed with a completely random blocks system. The results showed that nitrogen fertilization had an effect on the studied characteristics, where the ammonium sulfate treatment was superior to the rest of the treatments in plant heights, wet weight, and dry weight. Our results also showed that the ammonium sulfate treatment increased the availability and absorption of some nutrients in corn plants through its effect on the pH. The results also indicated that the highest productivity was in the treatment of ammonium sulfate, and the productivity reached (14.87) tons/ha.